Etiology in Pediatric Palliative Care: A Single Center Experience - Nilgün Harputluoğlu; Ünsal Yılmaz; Tanju Çelik (Galenos Publishing House, 2020)
INTRODUCTION: Pediatric palliative care is the highest level of care aimed at improving the quality of life of all children and families with life-limiting and threatening diseases. Characteristics of children needing pediatric palliative care in Turkey is unknown. The aim of this study was to investigate the characteristics and needs of children at pediatric palliative care. METHODS: Following the approval of local ethics committe, hospital records of children followed up at Dr. Behçet Uz Children's Hospital pediatric palliative care between November 2018 and November 2019 were retrospectively reviewed. RESULTS: A total of 97 patients were included into the study with a mean age of 5,2 +- 4,6 (0,3-17) years, and 53,6% (n = 48) of them were male. The most common diagnosis was cerebral palsy with 39.2% (n = 38) and congenital metabolic diseases with 20.6% (n = 20). The most common reason for hospitalization was lung infection (61.9%) and the most frequently used drugs were antibiotics (70.1%). In the first 7 days of hospitalization, the need for mechanical ventilator and child intensive care was significantly different (p = 0,020 and p = 0.020, respectively). DISCUSSION AND CONCLUSION: Children with a wide range of disorders, including cerebral palsy, metabolic disorders and muscle disorders, need pediatric palliative care. Lung infection is the most common reason for hospitalization, and patients who are hospitalized should be followed up more closely in the early period.